Penatalaksanaan Fisioterapi Pada Kasus Low Back Pain (LBPp) Akibat Scoliosis Dengan Modalitas Micro Wave Diathermy (MWD), Core Stabilitation Di RSUD Salatiga - Yuda Ariyanto, Dwi, Sugiono S.Fis,.MH.Kes (2015)
Background: Low Back Pain is a clinical syndrome characterized by the major symptoms of pain or feeling unwell lower spine area . Modality given in these conditions Micro Wave Diathermy ( MWD ) and Core Stabilization. Objective: To determine the effect of Micro Wave Diathermy ( MWD ) and core stabilization in reducing pain due to LBP , to determine the effect of Core Stabilization in the increased range of motion ( LGS ) on condition of LBP due to scoliosis . Methods: Physiotherapy methods used in the case that the modalities MWD and Core Stabilization . The evaluation was done by the method of measurement of pain ( VDS ) , the measurement of LGS ( tape measure ) . Results: After 6 times of therapy showed a decrease in tenderness T1 : not so heavily into T6 : mild , pain motion T1 : really heavy into T6 : not so heavy ; increase range of motion trunk , flexi T1 : 12 cm to T6 : 15 cm , T1 extension : 7 cm to T6 : 7 cm , lateral flexion right- T1 : 11 cm to T6 : 11 cm , left lateral flexion T1 : 9 cm to T6 : 9 cm . Conclusion: In that case the modalities MWD and Core Stabilization exercise can reduce pain and improve range of motion .